Influencia del contenido de humedad en las propiedades mecánicas de la madera Paliperro - Inga Reátegui, Marleni (2000)
Wood is a material that by its characteristics and properties is particularly versatile and suitable for the construccion_ however in our country and above all in our environment, the use of wood in construction and in many other applications is fairly limited because there is no technical information - available scientific that facilitates its use ingenieril_ this research work entitled "Influence of the content of humidity in the properties mechanical of the wood Paliperro" It has been prepared with the aim of solving one way or another the little existing information on this timber species, having as main objective the study of the influence of moisture content on their resistencia_ the experimental study of this research relating to trials physical and mechanical, it was developed entirely in the laboratory of test materials from the Faculty of engineering of the University national of Cajamarca complying...